2017
DOI: 10.1038/s41598-017-17357-3
|View full text |Cite
|
Sign up to set email alerts
|

Sodium fluoride exposure exerts toxic effects on porcine oocyte maturation

Abstract: Excessive long-term fluoride intake is associated with several health problems, including infertility. However, limited information is available on the toxic effects of fluoride exposure on the female reproductive system, especially oocyte maturation. In this study, we investigated the toxic effect of sodium fluoride (NaF) exposure on porcine oocyte maturation and its possible underlying mechanisms. Our results showed that NaF exposure during porcine oocyte maturation inhibited cumulus cell expansion and impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 65 publications
3
24
0
Order By: Relevance
“…Moreover, these factors are important determinants of the efficiency of embryo production in vitro. Indeed, these parameters decrease when oocytes are exposed to stresses such as aging (Lee et al, ), oxidative stress induced by H 2 O 2 or sodium fluoride (Liang et al, ; Yazaki, Hiradate, Hoshino, Tanemura & Sato, ), and heat stress induced by high temperature (Gharibzadeh et al, ). In this study, oocyte survival and PB extrusion rates were lower in the 0 AL group than in the control group, and these decreases were prevented in the 1 AL group (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these factors are important determinants of the efficiency of embryo production in vitro. Indeed, these parameters decrease when oocytes are exposed to stresses such as aging (Lee et al, ), oxidative stress induced by H 2 O 2 or sodium fluoride (Liang et al, ; Yazaki, Hiradate, Hoshino, Tanemura & Sato, ), and heat stress induced by high temperature (Gharibzadeh et al, ). In this study, oocyte survival and PB extrusion rates were lower in the 0 AL group than in the control group, and these decreases were prevented in the 1 AL group (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Oocyte quality is a key factor determining embryo competency, regardless of whether maturation occurs under normal or stress conditions. Oocytes whose quality is decreased by aging or exposure to oxidative stress have a reduced developmental potential (Lee et al, ; Liang et al, ). Consistent with this, we found that the blastocyst formation rate was significantly lower in the 0 AL group than in the 1 AL group.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors increase the developmental rate of oocytes (R. Li, Liu, Pedersen, & Callesen, ; Park, So, & Hyun, ; Shin et al, ). Oocytes damaged by aging or oxidative stress reportedly have a reduced developmental potential (Chaube et al, ; Goud et al, ; Liang et al, ). To investigate blastocyst quality, we checked the numbers of total and apoptotic cells per blastocyst.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors increase the developmental rate of oocytes (R. Li, Liu, Pedersen, & Callesen, 2015;Park, So, & Hyun, 2017;Shin et al, 2018). Oocytes damaged by aging or oxidative stress reportedly have a reduced developmental potential (Chaube et al, 2005;Goud et al, 2008;Liang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is part of the detrimental factors affecting oocyte developmental competence. Excessive oxidative stress will cause a series of damage to cells and leads to apoptosis (Liang et al ). Histone modification is also necessary for oocyte maturation, and aberrant histone modification could lead to the structural abnormalities between histone and DNA, which in turn affect gene expression and induce potential damage to oocyte (Huang et al ).…”
Section: Introductionmentioning
confidence: 99%